The Influence of Emotional Intelligence and Spiritual Intelligence on Job Satisfaction with Employee Performance as an Intervening Variable - Masitoh, Siti; Sudarma, Ketut (Universitas Negeri Semarang, 2019)
This study aims to analyze the effect of emotional intelligence, spiritual intelligence on job satisfaction through employee performance as an intervening variable. The sample in this study amounted to 92 employees. The sampling technique uses probability sampling with the type proportionate random sampling, which is a technique of taking samples of members of the population that is carried out proportionally. This research variable is derived from emotional intelligence, spiritual intelligence, employee performance, and job satisfaction. Analysis of the data used is descriptive percentage analysis, multiple linear regression analysis, coefficient of determination using SPSS 16, and path analysis. The results showed that partially emotional intelligence and spiritual intelligence had a positive and significant effect on employee performance, and had a positive and significant effect on job satisfaction. Employee performance has a positive and significant effect on job satisfaction. Employee performance is able to mediate the relationship of emotional intelligence and spiritual intelligence to job satisfaction. This research is expected to be included that is for companies to conduct training to improve emotional intelligence and spiritual intelligence, given the importance of these two variables in influencing the level of performance and employee job satisfaction.